Fruits and Vegetables Intake and Risk of Frailty in Women Aged 60 and Older (OR33-08-19). (13th June 2019) - Fung, Teresa; Stuijk, Ellen; Rodriguez-Artalejo, Fernando; Hagan, Kaitlin; Hu, Frank; Lopez-Garcia, Esther
Abstract: Objectives: Prior research has suggested that the anti-oxidative, and anti-inflammatory potential of fruits and vegetables may reduce pre-mature aging. The purpose of this analysis is to prospectively examine the association between fruits and vegetables intake and incident frailty in older women. Methods: 30, 267 non-frail women aged 60+ from the Nurses' Health Study were followed from 1990 to 2012. Frailty was defined as having at least three of the following five criteria from the FRAIL scale: fatigue, poor strength, low aerobic capacity, having ≥5 illnesses, and weight loss ≥5%. Fruits and vegetables intake were assessed from a food frequency questionnaire six times during follow-up and Cox models adjusting for potential confounders was used to estimate hazard ratios (HRs) and 95% confidence intervals for the association with incident frailty. Results: 6888 incident frailty cases were accrued during follow-up. Total fruits and vegetable intake was associated with a lower risk of frailty (adjusted RR comparing 7+ servings/d vs <3d/ = 0.77, 95% CI = 0.69–0.85, p trend < 0.001). The RR for total vegetables intake comparing 5+/d vs <2/d was 0.85 (95% CI = 0.77–0.94, p trend = 0.009). The strongest association among vegetables groups was observed with leafy vegetables (RR for >1/d compared with <1/wk = 0.77, 95% CI = 0.68–0.88, p trend < 0.001) and yellow vegetables (RR = 0.85, 95% CI = 0.74–0.98, p trend = 0.002). RR total fruits intake, comparing 4+/d vs <1/d was 0.91 (95%CI = 0.80–1.04, p trend = 0.03). intake of 6/wk or more of apples and pears was associated with an RR of 0.87 (95% CI = 0.78–0.98, p trend < 0.001) compared with women who consumed <1/wk. These associations did not differ by BMI or physical activity level. Conclusions: Higher fruits and vegetables intake was associated with a lower risk of frailty in this cohort of age 60+ U.S. women. Funding Sources: Data collection for this analysis was funded by the National Institutes of Health.